Determinan Kemiskinan Multidimensi Anak di Provinsi Nusa Tenggara Timur - Maria Septiani Gabur; Muhamad Andriansyah; Gloria Stephany Haman Cengga (Badan Pusat Statistik Provinsi NTT, 2024)
Poverty alleviation is one of the focuses of all countries in the world, including Indonesia. Based on BPS-Statistics Indonesia, monetary poverty in the age group of children (0-17 years) and toddlers (0-4 years) is higher than poverty in other age groups in 2022, which is 11.8 percent and 12.93 percent. Based on region, Nusa Tenggara Timur is the province with the highest child poverty after Papua, West Papua and Maluku, which is 25.68 percent. This study uses the MODA approach to determine the status of child poverty and multilevel binary regression to analyze the determinants of child poverty in Nusa Tenggara Timur Province. The results of the study showed that individual and household characteristics have a significant effect on multidimensional child poverty in Nusa Tenggara Timur Province. The individual characteristics that have an influence include the child's age and gender, while the household characteristics that have an influence are the Education of the Head of Household, Number of Household Members, Poverty Status of the Head of Household, Marital Status of the Head of Household, Household Recipient of Assistance, Head of Household with Disabilities, Households with Credit. In addition, the ICC value also shows that 98 percent of the diversity of multidimensional poverty status of children in Nusa Tenggara Timur Province is caused by differences in characteristics between districts/cities.